2015
DOI: 10.3906/biy-1408-47
|View full text |Cite
|
Sign up to set email alerts
|

Aspects of mycorrhizal colonization in adaptation of sweet marjoram (Origanum majorana L.) grown on industrially polluted soil

Abstract: The current study reveals the effects of mycorrhization on heavy metal uptake and accumulation, antioxidant potential, and essential oil composition of Origanum majorana L., grown on soil polluted with industrial Cd and Pb. Two strains of Claroideoglomus claroideum (EEZ 54 and EEZ 55) were isolated from soil that is naturally rich in metals. EEZ 35 (Funneliformis mosseae) was isolated from a place with industrial contamination. The percentage of mycorrhizal colonization with the EEZ 54 strain was higher than t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 39 publications
1
10
0
Order By: Relevance
“…There are contradictory data in the literature about how AM symbiosis influences the polyphenol content in the aerial parts of medicinal plants. Hristozkova et al 35 Glomus caledonium increased the rosmarinic acid content in the shoots of basil, while the others in this aspect remained ineffective 24 . In another study, similarly to the above mentioned, the inoculation with G. intraradices had no significant effect on polyphenolic content and profile of the leaves of basil, but increased the total anthocyanin concentration 44 .…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…There are contradictory data in the literature about how AM symbiosis influences the polyphenol content in the aerial parts of medicinal plants. Hristozkova et al 35 Glomus caledonium increased the rosmarinic acid content in the shoots of basil, while the others in this aspect remained ineffective 24 . In another study, similarly to the above mentioned, the inoculation with G. intraradices had no significant effect on polyphenolic content and profile of the leaves of basil, but increased the total anthocyanin concentration 44 .…”
Section: Discussionmentioning
confidence: 97%
“…In the terms of mycorrhizal status, marjoram, lemon balm and marigold belong to herbs forming symbiotic association with arbuscular mycorrhizal fungi. Earlier investigations also indicated that these plant species are colonized by a wide range of AMF [34][35][36][37][38][39][40] . Our results show that mycorrhization was significantly influenced by plant species.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To improve plant productivity performance, the mycorrhizal inoculation is a promising technology in sustainable agricultural systems already investigated also in aromatic herbs and recently, some interesting data were published on normal soils [199,200] and industrially polluted soil. [201] Heavy metal contaminated soils due to industrial activities are a major environmental problem that can reduce both the productivity of plants and the safety of plant products. Phytoremediation promoted by aromatic plants could be a promising method for removal of heavy metals from soil due their capability in terms of phytoextraction of metals with a negligible transfer of them to EOs.…”
Section: S Algeriensismentioning
confidence: 99%
“…Schneider et al [40] also investigated the role of mycorrhizal fungi on plant diversity and bioremediation in areas polluted with Pb observed a noticeable reduction in Pb uptake hence, subsequently recommending the use of the fungi for bioremediation techniques such as biostabilization. Similarly, Hristozkova et al [41] studied the effects of mycorrhization on the removal of Cd and Pb from a contaminated soil; the authors examined the effects of mycorrhizal fungi on the oil composition of Origanum majorana, as well as the antioxidant activity and the uptake and buildup of heavy metals by plants; they reported decreased uptake of Cd and Pb. Galli et al [42] reported reduction differences in Cu uptake among mycorrhizal and non-mycorrhizal Zea mays.…”
Section: Jhpr Volumementioning
confidence: 99%